1980
DOI: 10.1007/bf00403844
|View full text |Cite
|
Sign up to set email alerts
|

Variations in percutaneous absorption of testosterone in the rhesus monkey due to anatomic site of application and frequency of application

Abstract: This study determines if the anatomic region affected percutaneous absorption in the rhesus monkey, an animal model with some relevance to man. Percutaneous absorption of testosterone (13.3 microgram/cm2) from the ventral forearm was 8.8 +/- 2.5%. Absorption from the chest was slightly less (5.3 +/- 0.6%) while that from the cheek was about the same (9.6 +/- 0.2%). Absorption from the scalp was greatly increased (20.4 +/- 2.7%), that from the vagina was the greatest (63.1 +/- 2.6%). As previously noted in man,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 8 publications
4
17
0
Order By: Relevance
“…As shown for hydrocortisone, absorption from a single application of a high concentration was shown to be greater than the absorption of the same concentration divided into equal doses and applied separately (Wester et al, 1977b). These results were confi rmed with testosterone applied in a similar manner to studies with the rhesus monkey (Wester et al, 1980b). When testosterone was applied as a single dose of 13.3 μg cm −2 , total absorption was found to be 8.8%, while three consecutive applications of the same dose only resulted in a total absorption of 3.0%.…”
Section: Concentration and Frequencysupporting
confidence: 68%
See 1 more Smart Citation
“…As shown for hydrocortisone, absorption from a single application of a high concentration was shown to be greater than the absorption of the same concentration divided into equal doses and applied separately (Wester et al, 1977b). These results were confi rmed with testosterone applied in a similar manner to studies with the rhesus monkey (Wester et al, 1980b). When testosterone was applied as a single dose of 13.3 μg cm −2 , total absorption was found to be 8.8%, while three consecutive applications of the same dose only resulted in a total absorption of 3.0%.…”
Section: Concentration and Frequencysupporting
confidence: 68%
“…Consistent with regional patterns in dermal absorption, Ya-Xian et al (1999) reported the number of SC cell [1,6] Benzoic acid [2,3] Caff eine [3] Acetyl-salicylic acid [3] Hydrocortisone [4][5][6] Malathion [7] Parathion [7] TEWL †[8,9] [1] Wester et al (1980b); [2] Rougier et al (1986); [3] Rougier et al (1987a); [4] Feldmann and Maibach (1967);…”
Section: Variation In Absorption By Anatomic Sitementioning
confidence: 60%
“…We applied corticosteroids twice daily (except for day 1) since this is often the dermatologist's recommended dose in the treatment of ICD. However, studies comparing repetitive dosing to a single dose have failed to reveal increased absorption of corticoids with frequent dosing [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Skin absorption in the rhesus monkey is considered to be relevant to that of humans. Table 27.10 shows the percutaneous absorption of testosterone (Wester et al, 1980), fenitrothion, aminocarb, and diethyltoluamide (DEET) (Moody and Franklin, 1987;Moody, Benoit et al, 1998) in the rhesus monkey compared with the rat. For the rhesus monkey, there is regional variation between forehead (scalp) and forearm.…”
Section: Regional Variation In Human and Animal Pesticide Percutaneoumentioning
confidence: 99%